On the competition between six-membered and five-membered NHC towards alane centered ring expansion - Balayan, Kajal; Sharma, Himanshu; Vanka, Kumar; Ravindranathan, Sapna; Gonnade, Rajesh G.; Sen, Sakya S. (Chemical Communications, 2023)
The combination of 6-SIDipp center dot AlH3 (1) and 5-IDipp resulted in the ring expansion of 6-NHC, while the five-membered NHC remained unchanged, which was subsequently explained by DFT studies. Besides, the substitution chemistry of 1 was also studied with TMSOTf and I-2, which gave rise to the substitution of a hydride by triflate or iodide ligands.